STRATEGI “GERBANG PELANGI” DALAM MENGOPTIMALKAN PRESTASI SMA NEGERI 1 GANTUNG - Sabarudin Sabarudin (Khazanah Pendidikan, 2020)
ABSTRACT"Gerbang Pelangi" (Gerakan Pengembangan dan Penguatan Literasi, Sinergi raihPrestasi) as an alternative to solving problems in optimizing the achievements of SMA1 Gantung. The main focus of "Gerbang Pelangi" is to empower all schoolstakeholders in their daily activities by allocating available educational resources toachieve school achievements. Development of academic and non-academic schoolachievements through the "Gerbang Pelangi", carried out with three (3) mainprinciples, namely: (a) Development and strengthening of literacy into a realmovement and action, (b) Establish communication and synergy with various parties,and (c) Building a shared commitment to achieve both academic and non-academicachievements. The results of the "Gerbang Pelangi" implementation include: (a)Development and strengthening of literacy into a real movement and action (theformation of a school literacy team and the school literacy task force, theimplementation of extracurricular activities that support literacy skills, the formationof literacy classes, documented work of students in the literacy museums in schools,giving appreciation to educators, students and education personnel as well ascommunity elements in the form of the SMA 1 Gantung award, (b) Goodcommunication and synergy with various parties (growing commitment andcooperation from teachers, participants students, librarians, committees, parents tosupervise, monitor and ensure the sustainability of the school literacy program), (c)building a shared commitment to achievement (improving the quality of teacherperformance and learning quality of students become more meaningful to theemergence of creativity and courage of educators, educational staff education, studentsto continue working).Keywords: Gerbang Pelangi, school achievement.